The Benefits of Intensive Versus Standard Blood Pressure Treatment According to Fine Particulate Matter Air Pollution Exposure: A Post Hoc Analysis of SPRINT - Al-Kindi, Sadeer G.; Brook, Robert D.; Bhatt, Udayan; Brauer, Michael; Cushman, William C.; Hanson, Heidi A.; Kostis, John; Lash, James P.; Paine, Robert; Raphael, Kalani L.; Rapp, Stephen; Tamariz, Leonardo; et al. (Hypertension (Dallas, Tex. 1979), 2021)
Fine particulate matter <2.5 µm (PM2.5) air pollution is implicated in global mortality, especially from cardiovascular causes. A large body of evidence suggests a link between PM2.5 and elevation in blood pressure (BP), with the latter implicated as a potential mediator of cardiovascular events. We sought to determine if the outcomes of intensive BP lowering (systolic BP <120 mm Hg) on cardiovascular events are modified by PM2.5 exposure in the SPRINT (Systolic BP Intervention Trial). We linked annual PM2.5 exposure estimates derived from an integrated model to subjects participating in SPRINT. We evaluated the effect of intensive BP lowering by PM2.5 exposure on the primary outcome in SPRINT using cox-proportional hazard models. A total of 9286 participants were linked to PM2.5 levels (mean age 68±9 years). Intensive BP-lowering decreased risk of the primary outcome more among patients exposed to higher PM2.5 (Pinteraction=0.047). The estimate for lowering of primary outcome was numerically lower in the highest than in the lower quintiles. The benefits of intensive BP-lowering were larger among patients chronically exposed to PM2.5 levels above US National Ambient Air Quality Standards of 12 µg/m3 (hazard ratio, 0.47 [95% CI, 0.29–0.74]) compared with those living in cleaner locations (hazard ratio, 0.81 [95% CI, 0.68–0.97]), Pinteraction=0.037. This exploratory nonprespecified post hoc analysis of SPRINT suggests that the benefits of intensive BP lowering on the primary outcome was greater in patients exposed to higher PM2.5, suggesting that the magnitude of benefit may depend upon the magnitude of antecedent PM2.5 exposure.